Estudo das atividades antitumoral e imunoestimulante do polissacarídeo sulfatado isolado de Champia feldmannii Diaz-Pifferer (1977) - Lins, Kézia Oliveira Abrantes de Lacerda (2008)
Cancer is a desease that occurs in a larger number of people each year. The therapies used to treat it are still not satisfatory. Natural products have been studied to select new compounds capable of reducing tumours and with fewer side effects. The sulfated polysaccharide isolated from the seaweed C. feldmannii (Cf-PLS) was investigated for its antitumor and immunostimulating properties and also for the toxicological aspects related to Cf-PLS treatment. The Cf-PLS did not show any significant in vitro cytotoxic effect, but showed a strong in vivo antitumor effect. The inhibition rates of sarcoma 180 tumor development were 48.16 % and 48.62% at the doses of 10 and 25 mg/kg, respectively, and 68.32% when treated together with 5-fluorouracil (5-FU). The histopathological analysis of liver and kidney showed that the kidneys were affected by Cf-PLS-treatment, presenting some focal areas of acute tubular necrosis at the higher dose. Cf-PLS caused considerable changes in renal physiology, as shown by an increase in parameters such as perfusion pressure, renal vascular resistance, glomerular filtration rate, urinary flow and sodium, chloride and potassium excretion. Neither enzymatic activity of alanine aminotransferase, urea nor creatinin levels were significantly altered. In hematological analyses, leucopeny was observed after 5-FU treatment, but this effect was prevented when the treatment was associated with the Cf-PLS. It was also demonstrated that Cf-PLS acts as an immunomodulatory agent, raising the production of specific antibodies, and also increasing the production of OVA-specific antibodies. In addition, it induced a discreet increase of the white pulp and nest of megakaryocytic in spleen of treated mice and the neutrophil migration to the intraperitoneal cavity of mice. In conclusion, Cf-PLS has some interesting antitumour activity that could be associated with its immunostimulanting properties.